Prenatal nutrition among rural Bangladeshi pregnant women. - Basher, MS; Kabir, S; Ahmed, S; Miah, MA; Kamal, Ms (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):548-57 The abstract of this article is available on the PubMed website